Depressive symptoms and their influencing factors among older adults in China: a cross-sectional study - Hu, Xinyu; Liu, Huan; Liu, Qingwei; Yuan, Ting; Duan, Mengying; Luo, Yang; Min, Jiahui; Mei, Guangliang; Tao, Xiubin; Xuan, Bin; Zhang, Ming (Frontiers in Public Health, 2024)
BackgroundWith the acceleration of population aging, depressive symptoms in older adults have become an urgent global public health issue. It is critical to understand how to prevent and intervene the epidemic of depressive symptoms. Several studies have reported the prevalence of depressive symptoms among older adults in urban and rural China, but there is a lack of cross-sectional studies on the prevalence of depressive symptoms among older adults in Anhui Province after the COVID-19 pandemic.MethodsBetween December 2023 and February 2024, we used convenience sampling to randomly recruit 1,175 older people over 60 years old in Anhui Province, China. The PHQ-9 depressive symptom scale, frailty scale, and social frailty scale were used in the study. Logistic regression was used to analyze the association between frailty, social frailty, family health and depressive symptoms in older adults.ResultOf the 1,175 participants, 406 (34.6%) had depressive symptoms. Binary logistic regression results showed that Status of body pain (p < 0.001), Number of hospitalizations in the past year (p < 0.001), Status of social frailty (p < 0.001) and Status of frailty (p < 0.001) were highly correlated with depressive symptoms in older adults. While family health (OR = 0.53, 95% CI = 0.26–1.11, p = 0.092) was a protective factor for depressive symptoms in older adults.ConclusionThe prevalence of depressive symptoms among older adults is high in Anhui Province, China. Frailty, social frailty, and poor family health are associated with higher prevalence of depressive symptoms in older adults. Public health departments should pay more attention to the construction of mental health protection in the three environmental contexts of individual, family and society to promote healthy aging.